Developing an Indicator System for a Healthy City: Taking an Urban Area as a Pilot - Li T; Fang Y; Zeng D; Shi Z; Sharma M; Zeng H; Zhao Y (Dove Medical Press, 2020)
Tingting Li, 1–3 Yong Fang, 4 Dewei Zeng, 5 Zumin Shi, 6 Manoj Sharma, 7–9 Huan Zeng, 1–3 Yong Zhao 1 3, 10 1School of Public Health and Management, Chongqing Medical University, Chongqing 400016, People’s Republic of China; 2Research Center for Medicine and Social Development, Chongqing Medical University, Chongqing 400016, People’s Republic of China; 3The Innovation Center for Social Risk Governance in Health, Chongqing Medical University, Chongqing 400016, People’s Republic of China; 4Nan’an District Health Center for Woman and Children, Chongqing 400067, People’s Republic of China; 5Nan’an District Center for Disease Control and Prevention, Chongqing 400067, People’s Republic of China; 6Human Nutrition Department, College of Health Science, QU Health, Qatar University, Doha, Qatar; 7Department of Behavioral and Environmental Health, Jackson State University, Jackson, MS 39213, USA; 8Health for All, Omaha, NE 68124, USA; 9Health Sciences, Walden University, Minneapolis, MN 55401, USA; 10Chongqing Key Laboratory of Child Nutrition and Health, Children’s Hospital of Chongqing Medical University, Chongqing 400014, People’s Republic of ChinaCorrespondence: Yong Zhao; Huan ZengSchool of Public Health and Management, Chongqing Medical University, No.1, Medical School Road, Yuzhong District, Chongqing, People’s Republic of ChinaTel +86-138-8346-0842Fax +86 023 6848 5008Email zhaoyong@cqmu.edu.cn; huanzeng@cqmu.edu.cnPurpose: The Healthy Cities Project is an important strategy for global health. This study aimed to develop a scientific and appropriate indicator system for the evaluation of a Healthy City in Chongqing, China.Methods: Data were collected via a review of government documents, focus group discussions, and in-depth interviews. A total of 34 government documents were reviewed to build the indicator database based on our previous studies. The first round of focus group discussions, which involved eight health-related experts, was conducted to form the indicator system framework. In-depth interviews with 15 experts from government departments were conducted to design the improved indicator system. The second round of focus group discussions, which featured four experts, was conducted to obtain the final recommended list of indicators. A thematic framework was used to analyze the detailed interview notes.Results: The indicator system for the Healthy City consisted of 5 first-level indicators, 21 second-level indicators (e.g., health literacy), 73 third-level indicators (e.g., incidence of myopia), and three characteristic indicators. This indicator system spanned the scope of the environment, society, health services, healthy people, and health behaviors.Conclusion: This indicator system was based on the current status of the construction of the Healthy City in the pilot district. The indicator system could be dynamically adjusted according to the development of the Healthy City in the pilot district. Government departments play an important decision-making role in the development process of this indicator system.Keywords: healthy city, urban health, indicator system, health in all policy, public health, healthy China